Energy, exergy and economic analysis of an integrated solid oxide fuel cell – gas turbine – organic Rankine power generation system. (17th August 2016) - Eveloy, Valerie; Karunkeyoon, Wirinya; Rodgers, Peter; Al Alili, Ali
Abstract: To improve on-site power generation capacity and efficiency in energy-intensive process plants, the indirect integration of a standard gas turbine cycle with an internal reforming solid oxide fuel cell (SOFC) system and bottoming organic Rankine cycle (ORC) is investigated thermodynamically and economically. Among six ORC working fluids, namely toluene, benzene, cyclohexane, cyclopentane, R123 and R245fa, toluene is found to offer the best thermodynamic performance at favorable system size indicators. Using this fluid, the SOFC-GT-ORC system would enhance power generation capacity by a factor of three relative to the base gas turbine cycle, at energy and exergy efficiencies of approximately 64% and 62%, respectively. This represents efficiency improvements of approximately 34% compared with the base GT cycle, and of 6% relative to the hybrid SOFC-GT sub-system. The avoided purchase of natural gas and environmental emissions could generate net annual operating cost savings of five to nine million USD based on standard associated and sour gas prices, respectively, and would become profitable within three to six years, respectively. Highlights: Indirectly coupled SOFC – gas turbine (GT) – organic Rankine cycle (ORC). Six ORC working fluids evaluated. SOFC-GT-ORC electrical/exergy efficiencies of up to 64% and 62%, respectively. Integrated system economically viable for standard and sour gas prices.